The Impact of Self-directed Learning on Work Performance of Lawyers - Alonderienė, Raimonda; Suchotina, Nina (Organizations and Markets in Emerging Economies, 2017)
Lawyers mostly work individually and unobserved by supervisors, therefore, their employers want to make sure they gain sufficient competence to perform well. There is little previous research on the direct relationship between self-directed learning and individual work performance. Therefore, the goal of the paper is to analyze how self-directed learning influences individual work performance of lawyers in Lithuania.Our study is based on a quantitative research method, a self-reported questionnaire including 267 lawyers. The self-directed learning readiness (Guglielmino, adapted by Hashim, 2007) and individual task performance (Koopmans et al., 2012) scales were chosen. The correlation and regression analysis is performed to answer the question of the research.The survey revealed that self-directed learning dimensions explain up to 32.5 % of variance in individual work performance expressed by task performance. Determination, initiative, confidence and reflection in learning have statistically significant influence on individual work performan between self-directed learning and individual work performance of lawyers. Also, the topic is under-researched in the context of emerging economies.The paper is original as few if any previous studies analyze the relationship between self-directed learning and individual work performance of lawyers. Also, the topic is under-researched in the context of emerging economies.